Chapter 8 Mediatisation of science and the rise of promotional culture - Väliverronen, Esa (Taylor & Francis, 2021)
This chapter reviews the mediatisation concept, which has recently made a strong impact in media and communication studies, particularly in the field of political communication but also in science communication. It discusses the outcomes and problems of mediatisation research in relation to shifting science communication practices. The chapter introduces the concept of promotional culture in order to put the mediatisation of science into the broader social and cultural context of commercialisation and marketisation of research and universities. It argues that the adoption of quasi-corporative promotional practices in universities and research institutes poses a threat to academic freedom and the role of science as a public good.